Automated reasoning with analytic tableaux and related methods : 28th international conference, TABLEAUX 2019, London, UK, September 3-5, 2019 : proceedings /: 28th international conference, TABLEAUX 2019, London, UK, September 3-5, 2019 : proceedings. ([2019]) - Unknown
No abstract available